Kerusakan Lingkungan Akibat Tambang di Indonesia (Analisis Teologi Bencana Perspektif Hadis Nabi) - Bimba Valid Fathony; Muhammad Sidiq Pambudi; Fadhlan Ramadhani (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2026)
Indonesia is a country with abundant natural resource potential. Mining activities are the process of utilizing limited natural resources, where this activity can affect environmental damage. According to Islam, environmental damage is a direct result of irresponsible human actions towards nature. Because damaging the environment is detrimental to nature and has a negative impact on humans and other living things, Islam strictly forbids it. Islam teaches that the way humans interact with the environment reflects their level of faith and obedience. This study uses a qualitative research method using a descriptive approach. This study is a type of library research. Disaster theology according to the Prophet's hadith, especially in the problem of ecosystem damage due to mining activities in Indonesia, shows that natural disasters that occur are often related to sin and damage done by humans to the environment. The hadiths of the Prophet state that disasters such as earthquakes, floods, and various other disasters can be considered as warnings from Allah SWT for humans who violate moral norms and responsibilities in caring for the earth.